2014
DOI: 10.1186/1471-2156-15-31
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structuring of remnant forest patches in an endangered medicinal tree in North-western Ethiopia

Abstract: BackgroundHabitat loss and fragmentation may have detrimental impacts on genetic diversity, population structure and overall viability of tropical trees. The response of tropical trees to fragmentation processes may, however, be species, cohort or region-specific. Here we test the hypothesis that forest fragmentation is associated with lower genetic variability and higher genetic differentiation in adult and seedling populations of Prunus africana in North-western Ethiopia. This is a floristically impoverished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Morales et al (2015), suggest that the genetic population pattern found might be the result of a recent process of habitat fragmentation and loss. Genetic variation among adult tree plants may reflect prefragmentation effect, whereas contemporary gene flow patterns will be observable among seedlings (Yineger et al, 2014). Consequently, it would be interesting to contrast the genetic pattern found in adult trees with the genetic variability in seedlings of P. splendens, since new generations might reflect patterns of more restricted gene flow through seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Morales et al (2015), suggest that the genetic population pattern found might be the result of a recent process of habitat fragmentation and loss. Genetic variation among adult tree plants may reflect prefragmentation effect, whereas contemporary gene flow patterns will be observable among seedlings (Yineger et al, 2014). Consequently, it would be interesting to contrast the genetic pattern found in adult trees with the genetic variability in seedlings of P. splendens, since new generations might reflect patterns of more restricted gene flow through seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as these, in addition to others, such as habitat loss, reduction in population size, and loss of alleles, have the potential to cause limited seed dispersal among the extant populations. Indeed, our recent work (Yineger, Schmidt & Hughes, ) has demonstrated the potential limitation of gene flow among fragmented populations in north‐western Ethiopia, the current study region. However, this gene flow limitation was based on assessments of F ST and the proportion of first generation migrants as determined in GENECLASS, version 2.0 (Piry et al ., ), which does not take into account equilibrium conditions.…”
Section: Introductionmentioning
confidence: 81%
“…Details of the DNA isolation, amplification conditions, and allele scoring, as well as tests for null alleles, stuttering or large allele dropout, linkage disequilibrium and Hardy–Weinberg equilibrium, are reported in Yineger et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The pattern of increased diversity with age in brown trout was suggested to be a product of viability selection against inbred individuals that are less likely to survive to old age (Labonne et al., ). Genetic diversity in forest trees has also been shown to vary among age classes, with older trees exhibiting higher diversity than seedling cohorts, a pattern attributed to a negative impact of recent forest fragmentation on recruitment success (Kettle et al., ; Yineger, Schmidt, & Hughes, ).…”
Section: Discussionmentioning
confidence: 99%